Transforming Ecuadorian EFL Teacher Practices through Biography-Driven Instruction - Murry, Kevin G.; Holmes, Melissa Ann; Herrera, Socorro (My University, 2017)
The intensive English development/TESL program (TESL-GT) was created through a partnership between Ecuador and one Midwestern university. Through this program, Ecuador's Ministry of Education sought to enhance the instructional effectiveness of secondary English as a foreign language (EFL) teachers. The 67 Ecuadorian teacher participants in this study engaged in a 10-week pilot program. This program was aligned to the CREDE "Standards for Effective Pedagogy and Learning," which serve as universals (transnationally researched) standards of effective teaching practices. The 67 Ecuadorian program completers were subsequently observed in their Ecuadorian classrooms using the "Inventory of Situationally and Culturally Responsive Teaching" (ISCRT) rubric. Composite ISCRT scores were calculated as well as group means on each of the five standards reflected in the 22 indicators of the tool. Findings indicated unexpectedly robust levels of enactment of effective instructional practices for English learners. The significance of these findings and implications for teacher education are elucidated.